Comparison of Short-term Outcomes between Planned and Bailout Rotational Atherectomy in Patients with Calcified Coronary Artery Lesions - Khan, Md. Faisal Bin Selim; Uddin, Mir Jamal; Karmakar, Pradip Kumar; Rasel, Md. Mostafa-Al-; Firdaus, Hasina; Hasan, Mahmudul; Majumder, Md. Mizanur Rahman; Pal, Himel; Ali, Syed Mahmud; Hassan, Md. Rashidul (Cardiology and Cardiovascular Medicine, 2024)
Introduction: Percutaneous coronary intervention (PCI) of calcified coronary artery lesions remains challenging. Rotational atherectomy (RA) is useful device for plaque modification to facilitate balloon and stent delivery. Operators use either planned RA, defined as the initial strategy without previous device failure or bailout RA, defined as RA after device failure (lesions that cannot be crossed by a balloon or adequately dilated before stenting). Objective: To compare short-term outcomes between planned and bailout RA in patients with calcified coronary artery lesions. Methods: This Prospective observational study was conducted from April 2022 to September 2023 in the Department of Cardiology at National Institute of Cardiovascular Diseases (NICVD), Dhaka. A total of 60 patients who met the inclusion and exclusion criteria were enrolled in the study by consecutive sampling. Patients were divided into two groups: planned RA (n=30) and bailout RA (n=30). However, after 6 months of follow-up 4 respondents from bailout RA were lost to follow-up. The occurrence of major adverse cardiac events (MACE): death, myocardial infarction (MI), target vessel revascularizations (TVR) and stent thrombosis were recorded at 6 months of follow-up. Results: Procedural time, fluoroscopy time and contrast amount used were significantly reduced in the planned RA group compared to bailout RA group. Coronary dissection >5mm as higher in bailout RA (0.0% vs. 23.1%,p=0.005). However, no significant difference in in-hospital MACE was found between the two groups (6.71% vs.15.4%, p=0.401). After six-months follow-up, the incidence of Composite MACE in group I was lower than in group II (3.3% vs 15.3%, p=0.176) but it was not statistically significant (Kaplan-Meier estimates; hazard ratio [HR]: 3.265, 95% confidence interval: 0.866 to 12.317, p= 0.081). Conclusion: Planned RA was associated with a reduction in procedural duration, fluoroscopy time, contrast amount and procedural complications. But planned RA was not significantly associated with reduced Six-month MACE compared with bailout RA.